EXPLORING CONSUMER PREFERENCES AND FACTORS ASSOCIATED WITH VEGETABLE CONSUMPTION - Ubiparip Samek, Dragana; Bajić, Aleksandra; Pezo, Lato; Kovač, Renata; Mastilović, Jasna (Food and Feed Research, 2021)
The consumers’ preferences and their reasons for vegetable consumption were examined with the aim to provide useful information to increase the consumption of these food items. Consumers’ general viewpoints about vegetable consumption were examined using an online questionnaire. The study was conducted on a sample of 711 respondents chosen randomly and obtained data were analyzed by the correspondence analysis. Results suggest that consumers consider vegetables as tasty, easy to use and healthy for consumption. The main drawbacks for vegetable consumption are safety issues, short shelf-life and high price. In order to increase the consumption of these foodstuffs, each type of fresh and processed vegetable should have a specifically designed campaign, emphasizing its specific attribute. Obtained results might provide an insight into the current state of consumers’ behavior in Serbia and might be useful for creating specific promotional programs and more appropriate communication strategies aiming to increase consumers’ knowledge about the importance of regular vegetable consumption. They should raise consumers’ awareness by emphasizing the importance of adequate daily vegetable consumption. This, in turn, should improve public health and reduce the health and economic costs of massive chronic diseases caused by inadequate diet.